On-line collaborative learning for in-service teacher education - Salomão, Ana Cristina B. [UNESP] (Engineering and Technology Publishing, 2011)
This article brings some of the results of a study that analyzes a hybrid course for in-service teachers in the Project Teletandem Brazil: foreign languages for all. In this project, Brazilian teachers of Spanish as a foreign language took part in a blended tandem learning course, communicating via videoconferencing with Uruguayan teachers of Portuguese as a foreign language. The aim of the study was to verify Brazilian teachers' concepts and beliefs concerning language and culture and how the teletandem interactions affected them. After the interactions, teachers' views of culture seemed to also incorporate aspects of culture as an interpersonal process, instead of the factual and static view which was previously predominant. Therefore teacher education programs must consider the possibility of conjugating theory and reflective practice through the use of videoconference tools in order to allow teachers to experience culture rather learn facts about it. © 2011 ACADEMY PUBLISHER.
Keywords: Communication technology; Culture; Language teaching; Teacher education; Teletandem